Peran Attachment terhadap Self-Esteem pada Dewasa Muda Diselingkuhi - Breninda Junita Hasian; Jessica Ariela (Universitas Kristen Maranatha, 2020)
This study aims to see the effect of attachment on self-esteem in young adults who have been deceived in their relationship. This study was conducted on 113 participants with characteristics are between 20-40 years, had cheated when dating, and already have a new partner with dating or married status. The research method used is quantitative using online survey technique. The Experienced in Close Relationship Revised (ECR-R) used to measure attachments and Rosenberg's Self-Esteem Scale (RSES) used to measure self-esteem. In processing data using multiple regression. In addition, the results of correlation and different tests between demographic data relating to the variables are also explained in this study. Keywords: attachment, self-esteem, young adult, affair